Konseling Kelompok Untuk Mengurangi Kecemasan dalam Memasuki Dunia Kerja - Daroji, Daroji (Universitas Muhammadiyah Surakarta, 2015)
The purpose of this study is to determine the effectiveness of group counseling to reduce anxiety in entering the working world class XII student of Accounting SMK Negeri 1 Surakarta academic year 2013/2014.This research is a measure of guidance and counseling (PTBK). This study is conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. The subjects were students of class XII SMK Negeri 1 Surakarta Accounting totaling 9 students. Source of data derived from students. The data collection technique is by questionnaire and observation. The validity of the data using a triangulation method. Analyzed using percentages and clinical analysis. The results show that through group counseling can reduce anxiety entering the work of students from pre-cicle to the first cycle and from the first cycle to the second cycle. In the first cycle, the average percentage change of 28.05%. The anxiety of students has decreased, although not significantly. In the second cycle, the average percentage change of 51.91%, which means the results of the research has reached an indicator of success. The conclusions of this research are group counseling is effective for reducing anxiety enter the workforce in class XII student of Accounting SMK Negeri 1 Surakarta academic year 2013/2014.